Discrimination of alkyl and aromatic amine vapors using TTF–TCNQ based chemiresistive sensors. Issue 6 (5th January 2017) - Wang, Chen; Wu, Na; Jacobs, Daniel L.; Xu, Miao; Yang, Xiaomei; Zang, Ling
Abstract : Chemiresistors based on TTF–TCNQ microfibers can discriminate alkyl and aromatic amine vapors through the dramatic difference in signal recovery kinetics. Abstract : We report a chemiresistive sensor approach based on a TTF–TCNQ charge transfer material, which can real-time detect and distinguish the vapors of alkyl amine and aromatic amine species under ambient conditions, based on the dramatic difference in the kinetics of the electric current recovery processes after the exposure of the two amine species.